Abdominal muscle recruitment and PEEPi during bronchoconstriction in chronic obstructive pulmonary disease. Issue 4 (April 1997) - Gorini, M; Misuri, G; Duranti, R; Iandelli, I; Mancini, M; Scano, G
Abstract : BACKGROUND: It has been recently shown that, when breathing at rest, many patients with severe chronic obstructive pulmonary disease (COPD) contract abdominal muscles during expiration, and that this contraction is an important determinant of positive end expiratory alveolar pressure (PEEPi). In this study the effects of acute bronchoconstriction on abdominal muscle recruitment in patients with severe COPD were studied, together with the consequence of abdominal muscle action on chest wall mechanics. METHODS: Breathing pattern, pleural (PPL) and gastric (PGA) pressures, and changes in abdomen anteroposterior (AP) diameter were studied in 14 patients with COPD (mean forced expiratory volume in one second (FEV1) 1.06 (0.08) 1) under control conditions and during histamine-induced bronchoconstriction. RESULTS: The analysis of plots of PGA versus the AP diameter of the abdomen revealed that during maximal broncho-constriction (decrease in FEV1 of 34.8% (95% confidence intervals (CI) 29.9 to 39.7)) the expiratory rise in PGA increased significantly whereas end expiratory abdomen AP diameter decreased, indicating marked abdominal muscle recruitment. As a consequence, the rib cage compartment accounted for all of the volume of hyperinflation during bronchoconstriction (mean value 0.66 I, 95% CI 0.49 to 0.83). Positive end expiratory alveolar pressure during progressive bronchoconstriction was related directly to the expiratory rise in PGA and inversely to the expiratory time. CONCLUSIONS: The results indicate that, in patients with severe COPD, the abdominal muscles are recruited during acute bronchoconstriction. This recruitment probably preserves diaphragm length at the beginning of inspiratory muscle contraction despite the hyperinflation, and contributes significantly to positive end expiratory alveolar pressure. The degree of dynamic pulmonary hyperinflation during bronchoconstriction can be overestimated if abdominal muscle contraction is not assessed.